Diagnosis potential of subarachnoid hemorrhage using miRNA signatures isolated from plasma-derived extracellular vesicles - Sheng, Bin; Lai, Niansheng; Tao, Tao; Chen, Xiangxin; Gao, Sen; Zhu, Qi; Li, Wei; Zhang, Qingrong; Hang, Chunhua (Frontiers in Pharmacology, 2023)
The diagnosis and clinical management of aneurysmal subarachnoid haemorrhage (aSAH) is currently limited by lack of accessible molecular biomarkers that reflect the pathophysiology of disease. We used miRNAs (microRNAs) as diagnostics to characterize plasma extracellular vesicles in aSAH. It is unclear whether they can diagnose and manage aSAH. Next generation sequencing (NGS) was used to detect the miRNAs profile of plasma extracellular vesicles (exosomes) in three patients with SAH and three healthy controls (HCs). We identified four differentially expressed miRNAs and validated the results using RT-qPCR (quantitative real time polymerase chain reaction) with 113 aSAH patients and 40 HCs and 20 SAH mice model and 20 sham mice. Exosomal miRNA NGS revealed that six circulating exosomal miRNAs were differentially expressed in patients with aSAH vs HCs, and the level of four miRNAs (miR-369-3p, miR-410-3p, miR-193b-3p and miR-486-3p) were differentially significant. After multivariate logistic regression analysis, only miR-369-3p, miR-486-3p, and miR-193b-3p enabled prediction of neurological outcome. In a mouse model of SAH, greater expression of miR-193b-3p and miR-486-3p remained statistically significant relative to controls, whereas expression levels of miR-369-3p and miR-410-3p were lower. miRNA gene target prediction showed six genes associated with all four of these differentially expressed miRNAs. Circulating exosomes miR-369-3p, miR-410-3p, miR-193b-3p and miR-486-3p maybe influent intercellular communication and have potential clinical utility as prognostic biomarkers for aSAH patients.